(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
In the paper is described actual state of environment after brown-coal exploitation with open-pit and deep-boring methods. The results of recultivation- investigations are shown, which shown the problems of the strong acid lakes- recultivation. In the paper are also shown the geological and hydrogeological characteristics of the coal deposit area.